Estimating life standards in raramuri from 1905 to 2014 using anthropometric data. - Rivera Morales, Javier (Annals of Anthropology, 2020)
This work evaluates the changes in the living conditions of the Raramuri between 1905 and 2014. Anthropometric data were collected in the scientific literature (height, weight, cormic index and bmi) for adult men and women. These were compared with historical data from a sample of adolescents of both sexes, between 15 and 19 years old, obtained until 2014. No association of height and temporality was observed among the adults. Over the time period, men showed no association between weight (p = 0.397) and bmi (p = 0.368), while in women, weight (p = 0.013) increases. The data in adolescents show similar trends to that of the adults. It is not possible to observe sufficient positive effects to modify the health and nutrition processes reflected in the height of the adult. Some positive effects have been seen in childhood, while in the case of women the articulation of sociocultural and economic processes has led to overweight.